2022
DOI: 10.1183/23120541.00591-2021
|View full text |Cite
|
Sign up to set email alerts
|

Mortality and survival in idiopathic pulmonary fibrosis: a systematic review and meta-analysis

Abstract: Background: There are substantial advances in diagnosis and treatment for idiopathic pulmonary fibrosis (IPF), but without much evidence available on recent mortality and survival trends.Methods: A narrative synthesis approach was used to investigate the mortality trends, then meta-analyses for survival trends were carried out based on various time periods.Results: Six studies reported the mortality data for IPF in 22 countries, and 62 studies (covering 63 307 patients from 20 countries) reported survival data… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
20
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 40 publications
(27 citation statements)
references
References 93 publications
0
20
0
Order By: Relevance
“…However, in idiopathic pulmonary fibrosis (IPF), the normal honeycomb structure of alveoli is replaced by fibrotic tissue, resulting in reduced gas exchange in early stages of the disease, which ultimately leads to death from pulmonary failure. IPF is essentially an intractable disease, although some headway has been made with antifibrotics: 5-year cumulative survival rates are 51.4% for people taking antifibrotics versus 43.9% for people not taking these drugs ( 1 ), and a 2.5%–4.3% reduction in the decline of forced viral capacity was reported across various antifibrotics in a recent meta-analysis ( 2 ). Even with current therapeutics, the prognosis for IPF patients is worse than for most cancers, including lung cancer.…”
Section: Idiopathic Pulmonary Fibrosismentioning
confidence: 99%
“…However, in idiopathic pulmonary fibrosis (IPF), the normal honeycomb structure of alveoli is replaced by fibrotic tissue, resulting in reduced gas exchange in early stages of the disease, which ultimately leads to death from pulmonary failure. IPF is essentially an intractable disease, although some headway has been made with antifibrotics: 5-year cumulative survival rates are 51.4% for people taking antifibrotics versus 43.9% for people not taking these drugs ( 1 ), and a 2.5%–4.3% reduction in the decline of forced viral capacity was reported across various antifibrotics in a recent meta-analysis ( 2 ). Even with current therapeutics, the prognosis for IPF patients is worse than for most cancers, including lung cancer.…”
Section: Idiopathic Pulmonary Fibrosismentioning
confidence: 99%
“…A recent systematic review reported significantly better survival among those taking antifibrotics [6].…”
Section: Introductionmentioning
confidence: 99%
“…A recent systematic review reported significantly better survival among those taking antifibrotics [ 6 ]. With longer survival comes the need to more effectively manage the disease.…”
Section: Introductionmentioning
confidence: 99%
“…Within the complex landscape of interstitial lung diseases (ILDs), a widely studied disease and a major new concept have emerged with the publication of the updated 2022 ATS/ERS/JRS/ALAT clinical practice guideline: progressive pulmonary fibrosis (PPF). ( 1 ) While idiopathic pulmonary fibrosis (IPF) is a diagnosis of exclusion, with an unknown etiology and a grim prognosis rivaling most cancers, ( 2 ) PPF includes a multitude of ILDs, of both known and unknown origin, that share a progressive disease behavior.…”
Section: Introductionmentioning
confidence: 99%